Hominin geographical range dynamics and relative brain size: Do non-human primates provide a good analogy?. Issue 87 (October 2015) - MacDonald, Katharine; Smaers, Jeroen B.; Steele, James
Abstract: We use climatic and satellite remote sensing data to characterize environmental seasonality in the geographical ranges of extant non-human primates in order to assess the effect of relative brain size on tolerance of more seasonal habitats. Demonstration of such an effect in living non-human primates could provide a comparative framework for modeling hominin dispersals and geographical range dynamics in the Pliocene and Pleistocene. Our analyses found no such effect: there are neither positive nor negative correlations between relative brain size and either geographical range size or the average and range of values for environmental seasonality, whether analysed at the level of all primates, or within parvorders (strepsirrhine, catarrhine, platyrrhine). Independent analyses by other researchers comparing feeding behaviour and ecology at individual primate study sites demonstrate that in seasonal environments, the year-round metabolic costs of maintaining a relatively large brain are met by adaptive behavioural/dietary strategies. However, consistent with our own results, those comparative studies found that there was no overall association, whether positive or negative, between 'raw' environmental seasonality and primate relative brain size. We must therefore look elsewhere for a comparative model of hominin geographical range dynamics in the Pleistocene.